The impact of SO2 emissions trading scheme on pollution abatement and labor market for industrial enterprises in China - Zhang, Weijie; Zhang, Panpan; Niu, Xiaodi (Frontiers in Environmental Science, 2024)
To cope with the emissions permit trading program, industrial firms need to change production decisions, which may affect their pollution discharge, labor demand and worker's wage earnings. Using a time-varying difference-in-differences framework together with robustness checks, the research explores the impacts of the SO2 emissions trading scheme (SETS) on SO2 emissions, employments and wages of industrial firms in China. It was noted that the program resulted in a remarkable decline not merely in SO2 emissions but also in labor demands and wages. The mechanism analyses further show that emissions reduction is mainly driven by fossil energy input decrease rather than desulfurization technology. The negative effects of employments and wages are driven by the negative output effect and insufficient innovation technology rather than environmental substitute effect. Our findings contribute to the improvement of the market-oriented environmental permit trading program and development of regulated firms in developing countries.